Thrombocytopenia with bleeding manifestations in childhood malaria - Mohan, Kriti; Omar, B J; Singh, Rupa D; -, Aaradhana; Sachan, Ravi (Indian Journal of Child Health, 2016)
Background: Thrombocytopenia is frequently found in malaria, but its prognostic value has not been addressed in children. Bleeding with thrombocytopenia in malaria is not so common but can be a cause of mortality if left unattended. Objective: To study the occurrence and severity of thrombocytopenia with bleeding manifestations in children with malaria. Materials and Methods: This cross-sectional study was conducted in a pediatric hospital of north India. All positive cases of malaria <15 years of age admitted to the hospital between January 2008 and December 2013 were included in the study, and data were recorded on pre-designed pro forma. Patients were further assessed for thrombocytopenia and bleeding manifestations. Data were analyzed by Chi-square test and independent sample t-test using SPSS version 16. Results: Total 185 cases were included in the study with a median age of presentation of 4 years. Plasmodium vivax was identified in 142 (77%) patients, whereas Plasmodium falciparum in 31 (17%) and mixed infection in 12 (6%) patients. Thrombocytopenia was observed in 79 (43%) cases, of which 35 (44%) cases had mild, 30 (38%) cases moderate, and 14 (18%) cases had severe thrombocytopenia. Total 10 (5.4%) patients had bleeding manifestations, and all of these had thrombocytopenia. The most common bleeding manifestation was gastrointestinal bleeding presenting as malena. No significant association was found between bleeding and severity of thrombocytopenia (p=0.527) or species of malaria (p=0.682). Furthermore, no significant association was found between severity of malaria and thrombocytopenia (p=0.365). Conclusion: Thrombocytopenia and bleeding were not significantly associated with the type of malaria. In an endemic area, if a child presents with acute fever and thrombocytopenia with or without bleeding manifestation, diagnosis of malaria should be strongly suspected.